Friction and Wear Properties of Copper/Carbon/RB Ceramics Composite under Electrical Current - Kei Shibata (Japanese Society of Tribologists, 2009)
Friction and wear properties of the copper/carbon/RB ceramics (Cu/C/RBC) composite were investigated under electrical current with and without arc-discharge. The weight fraction and the mean diameter of RB ceramics powder were 5 wt% and 4.9 μm, respectively, in the Cu/C/RBC composite. Friction tests were conducted with the block-on-ring friction apparatus. The Cu/C/RBC and the copper/carbon (Cu/C) composite, the conventional pantograph slider material of a railway current collector, were used as block specimens. Under electrical current without arc-discharge, the Cu/C/RBC composite showed 98% reduction in the specific wear rate of the block specimen, 23% reduction in that of the ring specimen, and 75% reduction in the friction coefficient over the conventional Cu/C composite. Under electrical current with arc-discharge, the Cu/C/RBC composite showed the wear resistance to arc-discharge equivalent to the conventional Cu/C composite.